The Capacitive Behaviors ofManganese Dioxide Thin-Film Electrochemical Capacitor Prototypes - Pang, Suh Cem; Wee, Boon Hong; Chin, Suk Fun (Hindawi Publishing Corporation, 2011)
We have documented the fabrication of manganese dioxide (MnO2) thin-film electrochemical capacitor (EC) prototypes with dual-planar electrode configuration. These EC prototypes exhibited good capacitive behaviors in mild Na2SO4 aqueous electrolyte. Enhanced capacitive behaviors of EC prototypes were observed upon prolonged voltammetric cycling which could be associated with microstructural transformation ofMnO2 thin-film electrodes fromdensely packed plate-like to irregular petal-like surface morphology. Effects of voltammetric scan rates, prolonged voltammetric cycling, electrolyte composition, and electrolyte concentration on the surface morphology of MnO2 thin-film electrodes, and associated capacitive behaviors of MnO2 thin-film EC prototypes were investigated by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and galvanostatic charge/discharge (GCD) techniques. Results of both CV and EIS indicated that thin-film MnO2 EC prototypes exhibited the highest specific capacitance of 327 F/g in 0.2MNa2SO4 aqueous electrolyte. Being environmentally benign and cheap,MnO2 thinfilm electrochemical capacitors have high potential utility as pulsed power sources, as well as load-leveling functions in various consumer electronic devices.